Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the Ocean Drilling Program 1989
DOI: 10.2973/odp.proc.sr.104.134.1989
|View full text |Cite
|
Sign up to set email alerts
|

The Petrology of the Lower Series Volcanics, ODP Site 642

Abstract: Between 1086.6 and 1229.4 m below seafloor at Site 642 on the Outer Wring Plateau, a series of intermediate volcanic extrusive flow units and volcaniclastic sediments was sampled. A mixed sequence of dacitic subaerial flows, andesitic basalts, intermediate volcaniclastics, subordinate mid-ocean ridge basalt, (MORB) lithologies, and intrusives was recovered, in sharp contrast to the more uniform tholeiitic T-type MORB units of the overlying upper series. This lower series of volcanics is composed of three chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…Groves et al 1978). Some partial analogues of these settings do occur in postArchaean time: for instance, the c. 1.1 Ga basalt • rhyolite and sediment-filled Keweenawan rift of North America (Green 1977;Behrendt et al 1988;Ojakangas et al 2001), the complex volcanic rifted V6ring margin off the coast of Norway (Eldholm et al 1989;Parson et al 1989;Reemst & Cloetingh 2000), and perhaps the collapsed marginal basin of the Cretaceous Rocas Verdes Complex, Chile (e.g. Tarney et al 1976).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Groves et al 1978). Some partial analogues of these settings do occur in postArchaean time: for instance, the c. 1.1 Ga basalt • rhyolite and sediment-filled Keweenawan rift of North America (Green 1977;Behrendt et al 1988;Ojakangas et al 2001), the complex volcanic rifted V6ring margin off the coast of Norway (Eldholm et al 1989;Parson et al 1989;Reemst & Cloetingh 2000), and perhaps the collapsed marginal basin of the Cretaceous Rocas Verdes Complex, Chile (e.g. Tarney et al 1976).…”
Section: Discussionmentioning
confidence: 95%
“…Wendt et al 1997;Turner & Hawkesworth 1998), the occurrence of calc-alkaline dacites with Nb depletions in Iceland's central volcanoes (Jdnasson et al 1992), and the occurrence of dacites and andesites in extensional environments (e.g. Parson et al 1989). Hence, given the known complexity of modern processes, the non-uniqueness of many geochemical signatures, and the incomplete preservation of ancient environments, are we not overinterpreting the Archaean record in terms of simple end-members?…”
Section: Geochemical Constraandtsmentioning
confidence: 98%
“…Lavas collected in the 642E core on the Vøring Plateau (Figure a) consist of an Upper Series (US) of tholeiitic E‐MORB‐type basalts, and a very heterogeneous Lower Series (LS) that comprises rhyolitic ignimbrites, tholeiitic basalts, basaltic andesites, and dacites [ Viereck et al ., 1988, ; Parson et al ., ]. Based on trace elements and Sr‐Nd isotope data, Viereck et al .…”
Section: Discussionmentioning
confidence: 99%
“…[1988, ], Parson et al . [], and Meyer et al . [] concluded that the 642E US lavas are mostly uncontaminated and have essentially preserved the trace element and isotopic signature imprinted by a mantle source somewhat more radiogenic than the depleted MORB mantle (DMM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation